Circulating miR-148b-3p and miR-409-3p as biomarkers for heart failure in patients with mitral regurgitation - Chen, Mien-Cheng; Chang, Tzu-Hao; Chang, Jen-Ping; Huang, Hsien-Da; Ho, Wan-Chun; Lin, Yu-Sheng; Pan, Kuo-Li; Liu, Wen-Hao; Huang, Yao-Kuang (International journal of cardiology, 2016)
MicroRNAs (miRs) regulate gene expression in heart failure. Circulating miRs as biomarkers for heart failure in mitral regurgitation patients (MR) remain unexplored. This case–control study enrolled 32 MR patients with heart failure, 16 asymptomatic MR patients, and 12 control subjects without heart failure. We used next generation sequencing to study the gene expression profiles in the sera, and quantitative RT-PCR to study serum and tissue miRs in the left atria. Next generation sequencing analysis and enrichment analysis showed that 25 miRs were differentially expressed in the sera of MR patients with heart failure compared to control subjects. The circulating miR-148b-3p (p=0.002) and miR-409-3p (p=0.010) were significantly down-regulated in the MR patients with heart failure compared to control subjects. However, only circulation miR-148b-3p was significantly down-regulated in the MR patients without heart failure compared to control subjects (p=0.009). The tissue miR-409-3p was significantly down-regulated in the MR patients with heart failure compared to 3 purchased normal controls (p=0.041). Notably, the tissue RASGRP3 mRNA, target gene of miR-409-3p, was significantly up-regulated in the MR patients with heart failure compared to normal controls (p=0.010). The tissue FRY (p=0.010) and GADD45A (p=0.010) mRNAs, target genes of miR-148b-3p, were significantly up-regulated in the MR patients with heart failure compared to normal controls. Circulating miR-148b-3p might serve as biomarker for future development of heart failure and miR-409-3p might serve as biomarker for incident heart failure in MR patients.